Pengaruh Judi Online dan Lifestyle terhadap Perilaku Keuangan pada Masyarakat di Desa Banyuasih Kabupaten Karawang - Rudi Setyono Setyono; Ujang Suherman; Thomas Nadeak (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid transformation of digital technology has shifted social behavior paradigms, marked by the rise of online gambling phenomena and evolving lifestyles. These changes systematically hold the potential to influence the stability of individual financial behavior in both urban and rural areas. However, the extent to which online gambling and lifestyle determine rural financial behavior remains a discourse requiring in-depth investigation. This study aims to analyze the influence of online gambling and lifestyle on the financial behavior of the community in Banyuasih Village, Karawang Regency. Employing a quantitative approach with a causal method, data were gathered from 94 respondents selected through a simple purposive sampling technique. The research instrument, consisting of Likert-scale questionnaires, was analyzed using multiple linear regression via SPSS software. The results partially reveal that online gambling does not exert a significant influence on the community's financial behavior. Conversely, lifestyle is proven to have a positive and highly significant impact on financial behavior. Nonetheless, simultaneous testing confirms that online gambling and lifestyle collectively contribute significantly to the financial behavior patterns of the Banyuasih Village community. These findings underscore that lifestyle plays a far more dominant role in shaping the financial characteristics of rural communities compared to the impact of online gambling activities.